Digital Tranformation of MSMEs and Its Implications for Economic Resilience: A Qualitative Study Using NVivo (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the role of digital transformation in strengthening the economic resilience of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Despite their significant contribution to employment and GDP, MSMEs face uneven progress in adopting digital technologies due to limited literacy, inadequate infrastructure, and financial constraints. Employing a qualitative design, the research draws on in-depth interviews with four key stakeholders—Kominfo, Kemenkop UKM, the UMKM Association, and an economic analyst—and analyzes the data using NVivo 12 Plus through thematic coding, matrix queries, cluster analysis, and concept mapping. The findings highlight five major themes: (1) digital capacity building through literacy, training, and mentoring; (2) infrastructure readiness and accessibility, revealing disparities between urban and rural regions; (3) ecosystem integration and market access, emphasizing collaboration with e-commerce platforms; (4) financing challenges related to capital limitations, literacy gaps, and credit access; and (5) innovation and economic impact, demonstrating productivity gains, efficiency improvements, and market expansion. Cross-case and cluster analyses reveal complementary stakeholder roles, while concept mapping shows that digital innovation emerges from the synergy of capacity, infrastructure, ecosystem, and financing. The study concludes that MSME digitalization is a multi-layered process that enhances resilience by improving adaptability, productivity, and market reach, offering strategic insights for inclusive and sustainable policy frameworks.